2021
DOI: 10.1128/spectrum.00785-21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rapid Immunochromatographic Tests for the Direct Detection of Extended Spectrum Beta-Lactamases and Carbapenemases in Enterobacterales Isolated from Positive Blood Cultures

Abstract: The incidence of bloodstream infections (BSI) with extended spectrum beta-lactamase (ESBL) producing and carbapenemase producing Enterobacterales (CPE) is increasing at an alarming rate, for which only limited therapeutic options remain available. Rapid identification of these bacteria along with their antibiotic resistance mechanisms in positive blood cultures with Gram-negative bacteria will allow for early initiation of effective therapy and limit the overuse of broad-spectrum antibiotics in BSI (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…At present, some phenotypic-based identification methods, such as biochemical identification and bacterial identification system, are used to detect K. pneumoniae ( 7 , 8 ). Matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) was also commonly used to identify K. pneumoniae ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, some phenotypic-based identification methods, such as biochemical identification and bacterial identification system, are used to detect K. pneumoniae ( 7 , 8 ). Matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) was also commonly used to identify K. pneumoniae ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the CTX-M LFA had higher sensitivity than the ESBL NP test, while both tests had very high specificities. By comparison, the CTX-M LFA had a 91.6-100% sensitivity and a 95.0-100% specificity for direct testing of positive blood culture broths [13,14,[22][23][24][25][26][27]. In earlier study that used the CTX-M LFA to test positive clinical blood culture broths, the sensitivity and specificity were 100% (95% CI, 96.0-100%) and 99.6% (97.9-100%), respectively [14].…”
Section: Discussionmentioning
confidence: 97%
“…In our pilot testing, we found that false-negative or weak positive results may occur with some CTX-M producers in BC broths and that the issue can be resolved by adding this incubation step. In all previous studies that evaluate CTX-M LFA, testing was performed on cell pellets obtained from BC broths, thus involving centrifugation, removal of supernatant and resuspension [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, most previous studies performed CTX-M LFA after bacterial identification was obtained using the cell pellet from BC broth ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NG-Test CTX-M MULTI (CTX-M LFA) test (NG-Biotech Laboratories, France) is a lateral flow assay that is able to detect CTX-M producers rapidly in positive blood culture (BC) fluids [ 7 ]. However, most of the previous studies on direct detection of CTX-M producers from positive BCs were carried out after bacterial identification confirmed the presence of Enterobacterales and only a few species were tested [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. This study aimed to assess the diagnostic performance of the NG-CTX-M Test for direct detection of CTX-M producers in BCs positive for Gram-negative bacilli (GNB) before definitive identification.…”
Section: Introductionmentioning
confidence: 99%